2018
DOI: 10.31125/hunhemsire.454377
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelikte Mesleki Yetkinlik

Abstract: Yetkinlik bir kişinin görevleri doğru ve ustaca yapabilmesi için sahip olması gereken bilgi, beceri, yetenek, davranışlar ya da kapasitedir. Yetkinlik, hemşireler için önemli kriterlerdendir. Hemşirelikte yetkinlik çok boyutlu olduğundan üzerinde uzlaşılan ortak bir tanımı yoktur. Bilimsel yenilikler ve teknolojik gelişmeler hemşirelerin bu koşullara uyum sağlamasını, bakım gereksinimi ve beklentileri giderek artan hasta grubuna hizmet vermesini, farklı disiplinlerle bir arada çalışmasını ve çok sayıda hizmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
6
0
5
Order By: Relevance
“…Yapılan çalışmalarda, hemşirelerin kişilik özellikleri ile mesleğe ilişkin memnuniyet düzeyi arasında ilişki saptanmıştır (25)(26)(27) . Klinik alan deneyimi olan ve uzmanlaşmış hemşireler olaylara analitik olarak ele almaktadır, olasılıklar hakkında vizyon sahibidirler, bilgi ve deneyime dayalı sezgileriyle olayın bütününü kavrarlar ve olayları tahmin edebilirler (28) .…”
Section: Discussionunclassified
“…Yapılan çalışmalarda, hemşirelerin kişilik özellikleri ile mesleğe ilişkin memnuniyet düzeyi arasında ilişki saptanmıştır (25)(26)(27) . Klinik alan deneyimi olan ve uzmanlaşmış hemşireler olaylara analitik olarak ele almaktadır, olasılıklar hakkında vizyon sahibidirler, bilgi ve deneyime dayalı sezgileriyle olayın bütününü kavrarlar ve olayları tahmin edebilirler (28) .…”
Section: Discussionunclassified
“…With the use of the portfolio, students can reinforce their self-learning through their past experiences and motivate themselves for success and development (Yalabik & Musal, 2017). It is been reported that this method improves active learning in clinical settings, develops critical thinking, helps the assessment of professional competence, yet its objective evaluation is difficult (Karahan & Kav, 2018).…”
Section: Portfoliomentioning
confidence: 99%
“…Although there are various studies examining the relationship between resilience and mindfulness in the accessible literature, there is no study conducted on students studying in psychological counseling and guidance (PCG), social work and nursing undergraduate program to examine the relationship between these variables. Considering that individuals who study in the aforementioned programs will try to contribute to the awareness of people they will help in the future and to help increase their psychological resilience, it is thought that it is important to determine their mindfulness and resilience levels and whether there is a relationship between these variables (Akfırat, Öztan-Ulusoy and Kezer, 2018;Duyan, 2012;Karahan and Kav, 2018).…”
Section: Introductionmentioning
confidence: 99%